1981
DOI: 10.1007/bf01792420
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of peptide bond formation by polyribonucleotides on clay surfaces in fluctuating environments

Abstract: Summary. The condensation of glycine to form oligoglycine during temperature and moisture fluctuations on clay surfaces was enhanced up to fourfold by polyribonucleotides. Polydeoxyribonucleotides gave no enhancement. Yields were greatly reduced in the absence of clay. A small preference was observed among the polyribonucleotide bases with enhancements in the order of Poly G > Poly A = Poly U > Poly C at high density of polynucleotide on the clay surface and Poly G > Poly U > Poly C > Poly A at low density. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Beljanski et al (1968) identified a protein synthesizing system from Alcaligenesfaecalis that seems to utilize these esters as intermediates. Furthermore, a number of models for the origin of peptide synthesis and the genetic code involve internal-2'-aminoacyl esters of RNA Ikehara et al 1977;Nelsestuen 1978;Usher 1980;Dounce 1981;White and Erickson 1981). Our novel observation of stereoselective aminoacylation at the internal site suggests that these models should be studied more closely.…”
Section: Discussionmentioning
confidence: 81%
“…Beljanski et al (1968) identified a protein synthesizing system from Alcaligenesfaecalis that seems to utilize these esters as intermediates. Furthermore, a number of models for the origin of peptide synthesis and the genetic code involve internal-2'-aminoacyl esters of RNA Ikehara et al 1977;Nelsestuen 1978;Usher 1980;Dounce 1981;White and Erickson 1981). Our novel observation of stereoselective aminoacylation at the internal site suggests that these models should be studied more closely.…”
Section: Discussionmentioning
confidence: 81%
“…These surfaces have been experimentally shown to provide favorable conditions for possible prebiotic chemical reactions [25-27] (see also refs. [28-30], see refs.…”
Section: Discussionmentioning
confidence: 99%
“…Si-OH groups at clay particle edges are free to interact with amino acid carboxyl groups, leading to condensation reaction and ester formation. Such a reaction has been proposed to be an activation mechanism of amino acids for peptide bond formation (Jewett and Lawless 1981;White and Erickson 1981;Collins et al 1988;Basiuk et al 1991). In case of SWa-1 clay, the negative layer charge is localized on tetrahedra (Table 1).…”
Section: Glycine Reactionmentioning
confidence: 97%